1996
DOI: 10.1002/(sici)1098-2337(1996)22:5<345::aid-ab3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Parents' social problem-solving strategies in families with aggressive and non-aggressive boys

Abstract: This study examines the differences in social problem‐solving strategies among parents of aggressive and non‐aggressive boys. The subjects were the parents of 27 aggressive boys (27 mothers and 18 fathers) and of 28 non‐aggressive boys (26 mothers and 20 fathers). Social problem‐solving strategies were assessed from subject descriptions of six social problems arising in the daily lives of the adolescents. The results showed that the parents of both the non‐aggressive and aggressive boys helped their sons to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 36 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Several studies back up the role of some crucial variables of aggressive behaviour in applied educational and clinical settings: contingent attention upon aggressive responses, even in the form of reprimands, if the person has been deprived of social reinforcement; escape from aversive contingencies such as instructions or task demands; and acquisition of tangible reinforcers contingent on aggressive responses (Borrero et al, 2002;Carr et al, 1980;Iwata et al, 1994;Keller and Schoenfeld, 1979;Mace et al, 1991;Thompson and Iwata, 2001;Ò Reailly, 1995;Skinner, 1969;Ulrich, 1980). In addition, parental neglect in teaching compliance, triggers aversive and coercive interactions that increase antisocial responding as a result of chained contingencies of negative reinforcement; furthermore these behaviours generalise to school and peer contexts, where new strengthening contingencies appear (Biglan, 1995a, b;Coyne and Wilson, 2004;Huesmann et al, 2002;Kazdin and Buela, 1999;Knutson et al, 2004;Lipsey and Derzon, 1998;Mayer, 1995;Pakaslahti et al, 1996;Patterson, 1982Patterson, , 1986. Regarding adult subjects, Ullman and Krasner (1969) concluded that some possible factors underlying antisocial and psychopathic behaviours were: absence of a reinforcement history through which others become positive social reinforcers; insufficient training for performing appropriate social behaviour; to have been widely and physically punished; and positive reinforcement for performing antisocial behaviours from family and peers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies back up the role of some crucial variables of aggressive behaviour in applied educational and clinical settings: contingent attention upon aggressive responses, even in the form of reprimands, if the person has been deprived of social reinforcement; escape from aversive contingencies such as instructions or task demands; and acquisition of tangible reinforcers contingent on aggressive responses (Borrero et al, 2002;Carr et al, 1980;Iwata et al, 1994;Keller and Schoenfeld, 1979;Mace et al, 1991;Thompson and Iwata, 2001;Ò Reailly, 1995;Skinner, 1969;Ulrich, 1980). In addition, parental neglect in teaching compliance, triggers aversive and coercive interactions that increase antisocial responding as a result of chained contingencies of negative reinforcement; furthermore these behaviours generalise to school and peer contexts, where new strengthening contingencies appear (Biglan, 1995a, b;Coyne and Wilson, 2004;Huesmann et al, 2002;Kazdin and Buela, 1999;Knutson et al, 2004;Lipsey and Derzon, 1998;Mayer, 1995;Pakaslahti et al, 1996;Patterson, 1982Patterson, , 1986. Regarding adult subjects, Ullman and Krasner (1969) concluded that some possible factors underlying antisocial and psychopathic behaviours were: absence of a reinforcement history through which others become positive social reinforcers; insufficient training for performing appropriate social behaviour; to have been widely and physically punished; and positive reinforcement for performing antisocial behaviours from family and peers.…”
Section: Introductionmentioning
confidence: 99%
“…For identifying the causes of bullying and victimization, this research has focused on the study of cognitive and social-emotional processes as regulators and control mechanisms of aggressive behaviors. Aggressive children may have deficiencies in social determinants of aggression, problem-solving strategies [8], and empathy while interacting with others. Also, they have an urge to exhibit antisocial behaviors because they hold low selfefficacy beliefs [9].…”
mentioning
confidence: 99%